The New Norm of Learning: Implementing Learner-Centered Education with Technology Students - Ronas, Sunny May S.; Almonte, John Christian Rio; Arca, Jalfred B.; Padron, Reymart P. (Future Science / FSH-PH Publications, 2023)
This action research was conducted to determine the effect of interactive learning techniques in the motivational learning process among Bachelor of Science in Industrial Technology (BSIT) students of Cavite State University – CCAT Campus. The study utilized mixed research designs in the conduct of the study. Results showed an increase in students' cognitive, affective, and psychomotor domains after the intervention. This action research recommends utilizing coordinated-tandem teaching to maximize teaching delivery and address a huge volume of students and orienting the students to ICT/multimedia equipment to maximize online-lecture classes among BSIT Students.